SURGICAL SAFETY CHECKLIST: FROM IDEA TO PRACTICAL APPLICATION - A. L. Akopov; G. T. Bechvaya; A. A. Abramyan; E. V. Lotsman (Вестник хирургии имени И.И. Грекова)
Methods of surgical interventions performing, modifications, instruments used for operation became more developed every year. In spite of this fact, tendency of increase of the rate of iatrogenic errors took place and it was possible to prevent these mistakes by application of Surgical Safety Checklist. The «checklists» are easily available, not very expensive in practice and they are simple to use. An application of such questionnaires could improve the team work and understanding between members of the crew, which could influence directly on operation outcome. The article presents the history of creation of safety list, the analysis of efficacy of «checklist» application in clinical practice in different countries, information about controversial questions in «checklist», perspectives of its application.